2018
DOI: 10.18290/rpsych.2018.21.3-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of beliefs, motivation and entrepreneurial self-efficacy on entrepreneurial intentions: The moderating role of family support

Abstract: Entrepreneurship is crucial for promoting innovation, creating employment opportunities and generating social and economic wealth in a country's economy. In order to increase entrepreneurial activity, it is important to investigate entrepreneurial behavior by analyzing the process of businesses creation and the set of factors that favor the development of entrepreneurial aspirations, intentions and actions, which is a central goal ofpsychology of entrepreneurship. This research aims to deepen the knowledge abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 59 publications
(72 reference statements)
0
6
0
Order By: Relevance
“…The role of the social cognitive theory facilitates the individual's beliefs and develops a high level of self-efficacy toward engaging in the new business formation process [93,94]. Considering prior research in entrepreneurship [8] found that entrepreneurial self-efficacy mediates in the relationship between cognitive flexibility and entrepreneurial intention.…”
Section: Moderated-mediation Of Entrepreneurial Self-efficacymentioning
confidence: 99%
“…The role of the social cognitive theory facilitates the individual's beliefs and develops a high level of self-efficacy toward engaging in the new business formation process [93,94]. Considering prior research in entrepreneurship [8] found that entrepreneurial self-efficacy mediates in the relationship between cognitive flexibility and entrepreneurial intention.…”
Section: Moderated-mediation Of Entrepreneurial Self-efficacymentioning
confidence: 99%
“…ESE also mediates the influence of belief and motivation on EI. (Odoardi, Galletta, Battistelli, & Cangialosi, 2019). Educational institutions in Oman should develop courses that nurture ESE of the students.…”
Section: Discussionmentioning
confidence: 99%
“…Students who have high emotional support tend to have stronger entrepreneurial aspirations due to the belief that their families can support them during the various cycles of entrepreneurship, which are often unpredictable [54]. Students who receive from the families' support in the form of information regarding entrepreneurship have relatively vast knowledge leading them to become more confident in entrepreneurship [55], [56].…”
Section: Hypothesis Testingmentioning
confidence: 99%